Method for producing lactoferrin-containing products
Patent Information
- Application Number
- JP2024204300
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2044-11-22
AI Technical Summary
【0014】 本発明によれば、比較的簡易な工程で実施でき、選択性が高くかつコスト効率に優れ、工業的生産への適応性に優れた、ラクトフェリンを高純度で含有する製品の製造方法を提供できる。
Smart Images

Figure 0007635927000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a product containing lactoferrin at a high purity. [Background technology]
[0002] Lactoferrin, a type of whey protein, has been attracting attention as a functional ingredient with antibacterial and antibacterial properties. In addition to lactoferrin, whey also contains other major proteins, α-lactalbumin and β-lactoglobulin, and in particular, it is sometimes desirable to remove β-lactoglobulin from the perspective of reducing allergenicity. It is also sometimes desirable to remove casein, which is sometimes mixed with lactoferrin.
[0003] As techniques for removing β-lactoglobulin, several methods have been proposed, including thermal denaturation, electrical energy injection, crystallization, and also ion exchange.
[0004] Patent Document 1 states that lactoglobulin can be selectively removed by contacting a starting material containing whey protein with a strong base anion exchanger under specific conditions. Examples of the strong base anion exchanger used include those having a cross-linked agarose matrix, a cross-linked dextran matrix, a polystyrene matrix, or a polyacrylic matrix. There is no mention of the effect on lactoferrin.
[0005] Patent Document 2 describes that whey or concentrated whey can be passed through a column filled with an anion exchanger without adjusting its pH, and β-lactoglobulin can be selectively adsorbed to the anion exchanger. It describes that the anion exchanger used is a commercially available weakly basic anion exchanger, and that a weakly basic anion exchanger having a diethylaminoethyl group as the ion exchange group is preferable (
[0017] ). There is no mention of the effect on lactoferrin.
[0006] Patent Document 3 describes how whey proteins can be separated and recovered using a porous membrane that has functional groups that interact with proteins. Specifically, by passing whey through a porous membrane that has anion exchange groups, α-lactalbumin and β-lactoglobulin are selectively adsorbed, while lactoferrin is allowed to pass through without being adsorbed. The anion exchange groups used in this case are diethylamino groups (DEA, Et2N-) and quaternary ammonium groups (Q, R3N + In the separation and recovery using such a porous membrane, improvements are required in terms of processing efficiency and the complexity of the cleaning process.
[0007] Meanwhile, the present inventors have reported the use of a specific hydrophilic methacrylate-containing copolymer resin as an adsorbent for advanced glycation end products (AGEs) (Patent Document 4). Since then, no new uses have been proposed for this resin, and there is room for further development of applications. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 03-19654 [Patent Document 2] Japanese Patent Application Publication No. 06-62756 [Patent Document 3] JP 2010-193833 A [Patent Document 4] Patent No. 5053853 Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a method for producing a product containing highly pure lactoferrin, which can be carried out using relatively simple steps, is highly selective, has excellent cost efficiency, and is highly adaptable to industrial production. [Means for solving the problem]
[0010] The present invention comprises the following technical means. (1) A process for selectively adsorbing β-lactoglobulin to an anion exchange resin by contacting a raw material containing lactoferrin and β-lactoglobulin with the anion exchange resin, and a process for recovering a permeate that has permeated the anion exchange resin, The structural unit of the anion exchange resin is represented by the following formula [I] or [II]: [ka] [ka] It is expressed as In formula [I], m and n each represent a mole number, and the ratio of m to n is 40:60 to 80:20. R1 is an alkyl group having 1 to 4 carbon atoms; In formula [II], p and q represent the number of moles, and the ratio of p to q is 10:90 to 50:50; Y is a polyalkylenepolyamine residue. A method for producing a product containing lactoferrin at high purity.
[0011] (2) The method according to (1), wherein the raw material further contains casein, and the casein is also selectively adsorbed onto the anion exchange resin in the contact step.
[0012] (3) The method according to (1) or (2), wherein the anion exchange resin is an ethylene glycol dimethacrylate-crosslinked N-methylpyridylethylene copolymer or an ethylene glycol dimethacrylate-crosslinked triethylenetetramine-substituted glycidyl methacrylate copolymer.
[0013] (4) The method according to any one of (1) to (3), wherein the water content of the anion exchange resin is 40 to 90%. Effect of the Invention
[0014] According to the present invention, there is provided a method for producing a product containing lactoferrin at high purity, which can be carried out using relatively simple steps, is highly selective, has excellent cost efficiency, and is highly adaptable to industrial production.
[0015] Specifically, the present invention enables the highly selective removal of β-lactoglobulin from a raw material containing lactoferrin, and also enables the highly selective removal of β-lactoglobulin and casein from a raw material containing lactoferrin and casein. [Brief description of the drawings]
[0016] [Figure 1] 1 is a graph showing the results of measuring the water content of an anion exchange resin used in the present invention and a control resin. [Diagram 2] 1 is a graph showing the results of measuring the amount of β-lactoglobulin adsorbed on the anion exchange resin used in the present invention and a control resin. [Diagram 3] 1 is a graph showing the results of measuring the amount of lactoferrin adsorbed on the anion exchange resin used in the present invention and a control resin. [Figure 4] 1 is a graph showing the results of measuring the amounts of adsorption of lactoferrin and β-lactoglobulin-containing raw materials for the anion exchange resin used in the present invention and a control resin. [Diagram 5] 1 is a graph showing the results of measuring the amount of casein adsorbed for the anion exchange resin used in the present invention and a control resin. [Figure 6] 1 is a graph showing the results of measuring the adsorption amounts of each of the anion exchange resin used in the present invention and a control resin from a raw material containing lactoferrin and casein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below.
[0018] According to the manufacturing method of the present invention, a product containing lactoferrin at a high purity can be prepared. Here, "containing lactoferrin at a high purity" in the product means that the ratio of lactoferrin content to the total content of lactoferrin content and β-lactoglobulin content in the obtained product (lactoferrin content ÷ [lactoferrin content + β-lactoglobulin content] × 100 (%); hereinafter also referred to as "lactoferrin ratio") is significantly improved compared to the corresponding ratio in the raw material subjected to the manufacturing method of the present invention.
[0019] The proportion of lactoferrin in the product is preferably 10% or more, more preferably 20% or more, more preferably 30% or more, more preferably 40% or more, more preferably 50% or more, more preferably 60% or more, more preferably 70% or more, more preferably 80% or more, more preferably 90% or more, more preferably 95% or more.
[0020] The production method of the present invention includes a step of contacting a raw material containing lactoferrin and β-lactoglobulin with a specific anion exchange resin described in detail below (hereinafter also referred to as the "contact step"). By this step, β-lactoglobulin is selectively adsorbed to the anion exchange resin. The raw material includes, but is not limited to, raw milk, skim milk, whey protein, fractions thereof, or pre-treated products thereof.
[0021] With respect to the adsorption of β-lactoglobulin, the term "selectively" means that β-lactoglobulin is preferentially adsorbed onto the anion exchange resin over lactoferrin, and more specifically, that the adsorption amount per unit weight of the anion exchange resin is significantly higher for β-lactoglobulin than for lactoferrin.
[0022] The ratio of the amount of adsorbed β-lactoglobulin to the amount of adsorbed lactoferrin per unit weight of the anion exchange resin (adsorbed amount of β-lactoglobulin (mg / g) ÷ adsorbed amount of lactoferrin (mg / g)) is preferably 6 or more, more preferably 8 or more, more preferably 10 or more, more preferably 12 or more, more preferably 14 or more, more preferably 16 or more, more preferably 18 or more, and more preferably 20 or more.
[0023] The raw material used in the present invention may contain casein in addition to lactoferrin and β-lactoglobulin. In the production method of the present invention, preferably, in the same contact step, casein as well as β-lactoglobulin are selectively adsorbed onto the anion exchange resin. This allows efficient production of a product that is free from the desire for contamination with β-lactoglobulin and casein.
[0024] In this context, "containing lactoferrin at a high purity" in a product may also imply that the ratio of lactoferrin content to the total content of lactoferrin, β-lactoglobulin and casein in the resulting product (lactoferrin content ÷ [lactoferrin content + β-lactoglobulin content + casein content] × 100 (%)) is significantly improved compared to the corresponding ratio in the raw materials subjected to the present production method.
[0025] With respect to the adsorption of casein, "selectively" means that casein is preferentially adsorbed onto the anion exchange resin compared to lactoferrin, and more specifically, that the adsorption amount of casein per unit weight of the anion exchange resin is significantly higher than that of lactoferrin.
[0026] The ratio of the adsorption amount of casein to the adsorption amount of lactoferrin per unit weight of the anion exchange resin (adsorption amount of casein (mg / g) ÷ adsorption amount of lactoferrin (mg / g)) is preferably 60 or more, more preferably 80 or more, more preferably 100 or more, more preferably 120 or more, more preferably 140 or more, more preferably 160 or more, more preferably 180 or more, and more preferably 200 or more.
[0027] The production method of the present invention includes a step of recovering the permeate that has permeated the anion exchange resin following the contact step. The permeate may be recovered in its entirety, or a partial fraction thereof may be recovered in light of the properties of the raw material, etc. The recovered permeate may be subjected to further steps such as concentration and drying, as necessary.
[0028] The anion exchange resin used in the present invention has a structural unit represented by formula [I] or formula [II]. First, formula [I] is shown. [ka]
[0029] In formula [I], m and n represent the number of moles, and the ratio of m to n is 40:60 to 80:20, preferably 45:55 to 80:20, more preferably 50:50 to 75:25, more preferably 55:45 to 70:30, more preferably 60:40 to 70:30. The order of bonding between the molar number m (units derived from ethylene glycol dimethacrylate) and the molar number n (units derived from N-alkylpyridylethylene) is not limited.
[0030] In formula [I], R1 is an alkyl group having 1 to 4 carbon atoms, preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, more preferably a methyl group. A particularly preferred anion exchange resin is an ethylene glycol dimethacrylate crosslinked N-methylpyridylethylene copolymer.
[0031] Formula [II] is shown below. [ka]
[0032] In formula [II], p and q represent the number of moles, and the ratio of p to q is 10:90 to 50:50, preferably 15:85 to 50:50, more preferably 20:80 to 45:55, and more preferably 20:80 to 40:60. The order of bonding between the molar number p (units derived from ethylene glycol dimethacrylate) and the molar number q (units derived from polyalkylene polyamine-substituted glycidyl methacrylate) is not limited.
[0033] In formula [II], Y is a polyalkylene polyamine residue, and has a structure resulting from the reaction of polyalkylene polyamine with the glycidyl group of glycidyl methacrylate. Here, the polyalkylene polyamine is preferably a compound having three or more amino groups. Specific examples include diethylene triamine, triethylene tetramine, tetraethylene pentamine, pentaethylene hexamine, dipropylene triamine, tripropylene tetramine, and tetrapropylene pentamine. In producing an anion exchange resin, these can be used alone or in combination of two or more. A particularly preferred anion exchange resin is an ethylene glycol dimethacrylate crosslinked triethylene tetramine-substituted glycidyl methacrylate copolymer.
[0034] The anion exchange resin used in the present invention has a water content of preferably 40 to 90%, more preferably 45 to 85%, more preferably 50 to 80%, more preferably 55 to 75%, and more preferably 60 to 70%. It is believed that the relatively high water content and the soft structure of the resin contribute to the expression of the adsorption performance intended in the present invention. The water content is measured under the conditions specified in the following examples.
[0035] The anion exchange resin used in the present invention, in the case of a copolymer represented by formula [I], can be prepared, for example, by copolymerizing ethylene glycol dimethacrylate (EGDMA) and 4-vinylpyridine (4VP) in a polymerization dispersion medium, converting the copolymer into a quaternary ammonium salt with bromomethane or the like, and, if necessary, converting the copolymer into a salt with hydrochloric acid or the like. In the above polymerization reaction, the ratio of EGDMA to 4VP is appropriately set within a range in which the product resin satisfies m and n in formula [I].
[0036] The copolymer represented by formula [II] can be prepared, for example, by copolymerizing ethylene glycol dimethacrylate (EGDMA) and glycidyl methacrylate (GMA) in a polymerization dispersion medium, reacting the intermediate product with triethylenetetramine (TTA) to introduce a triethylenetetramine residue, and then, if necessary, converting it into a salt with hydrochloric acid or the like. In the above polymerization reaction, the ratio of EGDMA to GMA is appropriately set within a range in which the final product, the resin, satisfies p and q in formula [II]. The amount of TTA used is appropriately set according to the amount of units derived from GMA present in the intermediate product.
[0037] The production method of the present invention can be carried out either in a continuous manner using a column packed with an anion exchange resin or in a batch manner in which the anion exchange resin is charged into a treatment device.
[0038] The product containing lactoferrin at high purity obtained by the production method of the present invention may be in the form of a liquid such as an aqueous solution, or a solid such as a powder, but is not limited thereto. The product may be used in the form of a food, a food additive, a functional food, a cosmetic, a quasi-drug, or a pharmaceutical, but is not limited thereto. EXAMPLES
[0039] The embodiments of the present invention will be described more specifically below.
[0040] (Synthesis Example 1: Preparation and Evaluation of Ethylene Glycol Dimethacrylate Crosslinked N-Methylpyridylethylene Hydrochloride Copolymer) (1) Reagents Ethylene glycol dimethacrylate (EGDMA) was washed with 10% sodium hydroxide aqueous solution to remove the polymerization inhibitor, and then used for the polymerization reaction. It was stored in a nitrogen-substituted storage container until it was used for the reaction. 4-Vinylpyridine (4VP) was used after distillation under reduced pressure. The polymerization initiator, azobisisobutyronitrile (AIBN; special grade reagent), was used as is. EGDMA was purchased from Merck Ltd., and 4VP and AIBN were purchased from Fujifilm Wako Pure Chemical Corporation.
[0041] (2) Preparation of polymerization dispersion medium A polymerization dispersion medium was prepared by adding sodium chloride to a 0.5 w / v % aqueous solution of hydroxyethyl cellulose so that the concentration was 10 w / v %.
[0042] (3) Synthesis A 1000mL separable three-necked round-bottom flask equipped with a thermometer, a stirring device equipped with two stirring blades (blade diameter 80mm) made of Teflon (registered trademark), a Dimroth, and an argon inlet tube was charged with 500mL of polymerization dispersion medium. After stirring at 400 rpm for about 10 minutes under nitrogen gas flow, the stirring speed was adjusted to 300 rpm. Next, 100mg of AIBN was dissolved in 100mL of a mixture of EGDMA and 4VP mixed in a mass ratio of 80:20 to prepare a monomer mixture solution, and this mixture solution was injected into the polymerization dispersion medium.
[0043] After confirming that the spherical monomer phase was well dispersed in the polymerization dispersion medium under an optical microscope, the temperature was raised to 70°C over 30 to 40 minutes, and the mixture was kept at 70°C for 4 hours to polymerize. The temperature was further raised to 80°C, and the mixture was reacted for 1 hour, and then slowly cooled over 5 hours to obtain a reaction product. The reaction product was suction filtered, washed three times with hot deionized water, and further washed with an equal volume mixture of deionized water and methanol, and then dried at 60°C for 12 hours. The mixture was then dried under reduced pressure for 24 hours to obtain an ethylene glycol dimethacrylate crosslinked pyridyl ethylene copolymer.
[0044] The obtained copolymer was further reacted with bromomethane so that the mass ratio of copolymer to bromomethane was about 10: 1. The reaction product was then washed with an equal volume mixture of ionized water and methanol, and dried to obtain a free base polymer converted to quaternary ammonium.
[0045] Next, elemental analysis of the free base polymer was performed to measure the nitrogen content. Approximately 5 g of the free base polymer was placed in a 100 mL beaker, and deionized water was added to fully swell the polymer. Then, while stirring with a glass rod, 1N hydrochloric acid equivalent to 40 mol% of the measured nitrogen content was added. After leaving the polymer at room temperature overnight or more, the pH of the suspension supernatant was 5 to 6, and the supernatant did not become cloudy when 0.1 M silver nitrate was dropped into the supernatant, confirming that the polymer had been hydrochlorinated. The polymer was then washed with an equal volume mixture of ionized water and methanol, and then thoroughly dried to obtain an anion exchange resin, which is an ethylene glycol dimethacrylate crosslinked N-methylpyridylethylene hydrochloride copolymer (EGDMA-4VP) shown in formula [I] (where R1 is a methyl group).
[0046] The resulting EGDMA-4VP was analyzed using an elemental analyzer (MT-700HCN, Yanaco Analytical Industry Co., Ltd.) to find that it contained 57.81% carbon, 6.70% hydrogen, and 1.98% nitrogen.
[0047] (4) Moisture content measurement The moisture content of the resulting EGDMA-4VP was measured under the following conditions: Place 30 g of anion exchange resin in a centrifuge tube and centrifuge to dehydrate (3000 g for 15 minutes). · Dry the dehydrated resin in a constant temperature dryer (105℃ for 15 hours). After drying, cool to room temperature in a desiccator and measure the dry weight. Calculate the moisture content (%) from the weight loss before dehydration (i.e., the wet weight) according to the following formula [III]. (Water weight - dry weight) / resin weight × 100(%) ··· Formula [III] The "resin weight" refers to the weight of the resin immediately after dehydration and before drying. For comparison, the water content was determined under the same conditions for commercially available anion exchange resins, Diaion (registered trademark) SA-10A and SA-20A (both manufactured by Mitsubishi Chemical Corporation). The results are shown in Figure 1.
[0048] (Synthesis Example 2: Preparation and Evaluation of Ethylene Glycol Dimethacrylate Crosslinked Triethylenetetramine Substituted Glycidyl Methacrylate Copolymer) (1) Reagents Ethylene glycol dimethacrylate (EGDMA) was washed with 10% sodium hydroxide aqueous solution to remove the polymerization inhibitor, and then used for the polymerization reaction. It was stored in a nitrogen-substituted storage container until it was used for the reaction. Triethylenetetramine (TTA) was used after distillation under reduced pressure. Glycidyl methacrylate (GMA) was used as is. Azobisisobutyronitrile (AIBN; special grade reagent), a polymerization initiator, was used as is. EGDMA was purchased from Merck Ltd., TTA and GMA from Tokyo Chemical Industry Co., Ltd., and AIBN from Fujifilm Wako Pure Chemical Industries, Ltd.
[0049] (2) Preparation of polymerization dispersion medium A polymerization dispersion medium was prepared by taking 50 mL of an aqueous solution (viscosity approximately 5000 cps) containing 1 w / v% hydroxyethyl cellulose (Tokyo Chemical Industry Co., Ltd.), adding 6 g of sodium sulfate (Fujifilm Wako Pure Chemical Industries Co., Ltd.), and adding deionized water to bring the total volume to 500 mL.
[0050] (3) Synthesis 500 mL of the polymerization dispersion medium was placed in a 1000 mL capacity separable three-necked round bottom flask equipped with a thermometer, a stirring device equipped with two Teflon (registered trademark) stirring blades (blade diameter 80 mm), a Dimroth, and an argon inlet tube. After stirring at 400 rpm for about 10 minutes under a nitrogen stream, the stirring speed was adjusted to 300 rpm. Next, 0.6 g of EGDMA, 29.4 g of GMA, and 0.1 g of AIBN were mixed and poured into the polymerization dispersion medium.
[0051] After confirming under an optical microscope that the spherical monomer phase was well dispersed in the polymerization dispersion medium, the temperature was raised to 50°C over about 1 hour, and polymerization was carried out for 2 hours while maintaining the temperature at 50°C. The temperature was further raised to 80°C over about 30 minutes, and the reaction was carried out for 1 hour. The product was collected by suction filtration, washed three times with hot deionized water, and further washed with methanol. It was then dried at 60°C for 12 hours, and further dried overnight under reduced pressure in a desiccator.
[0052] Approximately 30 g of the dried product was placed in a sieve containing JIS 22, 30, 42, 60, 83, 100, 140, and 200 mesh sieves stacked in sequence, and shaken for 30 minutes to classify. The 100-42 mesh (149-355 μm) and 42-30 mesh (355-500 μm) fractions were collected and used for the following synthesis.
[0053] In a 200 mL pressure-resistant reaction vessel, 5 g of the above fraction, 12.5 mL of TTA, and 37.5 mL of 1,4-dioxane were placed, and after shaking well, the mixture was reacted in a water bath at 80 °C for 5 hours. The reaction product was transferred into deionized water and collected by suction filtration. The reaction product was placed in a glass column tube, washed with 0.1 N aqueous hydrochloric acid and 0.1 N aqueous sodium hydroxide solution in sequence, and washed with deionized water until the pH of the effluent reached 6 to 7. The reaction product was further washed with methanol while suctioning using a Buchner funnel with 5B filter paper. It was then dried at 60 °C for 12 hours, and further dried in a desiccator under reduced pressure for about 12 hours. The infrared absorption spectrum of the obtained polymer was measured using an IR-Tracer-100 (Shimadzu Corporation), and it was confirmed that it was an ethylene glycol dimethacrylate crosslinked triethylenetetramine-substituted glycidyl methacrylate copolymer.
[0054] Further, the copolymer was hydrochlorinated as follows. First, the ethylene glycol dimethacrylate crosslinked triethylenetetramine-substituted glycidyl methacrylate copolymer obtained above was subjected to elemental analysis to measure the nitrogen content. About 2 g of the copolymer was placed in a 50 mL Erlenmeyer flask, and deionized water was added to fully swell the copolymer. Then, 1N hydrochloric acid was added dropwise in an amount corresponding to the measured nitrogen content while stirring with a glass rod. After leaving the copolymer at room temperature for about 12 hours, the reaction solution was suction filtered using a Buchner funnel using 5B filter paper, and the residue was washed with methanol. Then, the mixture was dried at 60°C for 12 hours, and further dried in a desiccator under reduced pressure for about 24 hours to obtain an anion exchange resin that is an ethylene glycol dimethacrylate crosslinked triethylenetetramine-substituted glycidyl methacrylate copolymer (referred to as EGDMA-TTA / GMA).
[0055] (4) Moisture content measurement The water content of the resulting EGDMA-TTA / GMA was measured under the same conditions as in Synthesis Example 1. The results are also shown in FIG.
[0056] (Experimental Example 1: Preliminary experiment on β-lactoglobulin adsorption by anion exchange resin) An aqueous solution of β-lactoglobulin was prepared at a concentration of 3 g / L. 10 g of EGDMA-4VP obtained in the synthesis example was added as a resin per 100 mL of this aqueous solution, and the mixture was stirred at 25° C. for 30 minutes. The mixture after the treatment was filtered through filter paper, and the filtrate was centrifuged (5000 g). The residual concentration of β-lactoglobulin in the supernatant obtained by centrifugation was measured by ELISA (enzyme immunoassay; bovine β-lactoglobulin measurement kit (Funakoshi Co., Ltd.)) using anti-β-lactoglobulin antibodies. The amount of β-lactoglobulin adsorbed to the resin was calculated from the difference between the initial concentration and the residual concentration of β-lactoglobulin. For comparison, the adsorption amounts were determined under the same conditions using SA-10A and SA-20A as resins. The results are shown in Figure 2.
[0057] (Experimental Example 2: Preliminary experiment on lactoferrin adsorption by anion exchange resin) An aqueous solution of lactoferrin (iron saturation 19%) was prepared at a concentration of 0.3 g / L. 5 g of EGDMA-4VP obtained in the synthesis example as a resin was added per 100 mL of this aqueous solution, and the mixture was stirred at 25°C for 30 minutes. The mixture after the treatment was filtered through filter paper, and the filtrate was centrifuged (5000 g). The residual lactoferrin concentration of the supernatant obtained by centrifugation was measured by ELISA using an anti-lactoferrin antibody (using a bovine lactoferrin measurement kit (Funakoshi Co., Ltd.)). The amount of lactoferrin adsorbed to the resin was calculated from the difference between the initial lactoferrin concentration and the residual concentration. For comparison, the adsorption amounts were determined under the same conditions using SA-10A and SA-20A as resins. The results are shown in Figure 3.
[0058] (Examples 1-2 and Comparative Examples 1-2: Adsorption treatment of raw materials containing lactoferrin and β-lactoglobulin using an anion exchange resin) An aqueous solution containing lactoferrin and β-lactoglobulin was prepared with a lactoferrin concentration of 0.3 g / L and a β-lactoglobulin concentration of 3 g / L. 10 g of EGDMA-4VP or EGDMA-TTA / GMA obtained in the synthesis example was added per 100 mL of this aqueous solution as a resin, and the mixture was stirred at 25°C for 30 minutes. The mixture after the treatment was filtered through a filter paper, and the filtrate was centrifuged (5000 g). The residual concentrations of lactoferrin and β-lactoglobulin in the supernatant obtained by centrifugation were measured by the ELISA method (described above) using anti-lactoferrin antibody and anti-β-lactoglobulin antibody, respectively. The amount of lactoferrin and β-lactoglobulin adsorbed to the resin was calculated from the difference between the initial concentration and the residual concentration (Examples 1 to 2). For comparison, the adsorption amounts were determined under the same conditions using SA-10A and SA-20A as resins (Comparative Examples 1 and 2). The results are shown in FIG. 4 (the ratio of the amount of adsorbed β-lactoglobulin to the amount of adsorbed lactoferrin is shown in the margin).
[0059] (Experimental Example 3: Preliminary experiment on casein adsorption using anion exchange resin) An aqueous solution of casein was prepared with a concentration of 20 g / L (the concentration of casein in milk is about 27 g / L). 10 g of EGDMA-4VP obtained in the synthesis example was added per 100 mL of this aqueous solution, and the mixture was stirred at 25°C for 30 minutes. The mixture after the treatment was filtered through filter paper, and the filtrate was centrifuged (5000 g). The residual casein concentration of the supernatant obtained by centrifugation was measured by ELISA (enzyme immunoassay; Morinaga FASPEK ELISA II Milk (Casein) Kit (Morinaga Biological Science Institute, Inc.)) using an anti-casein antibody. The amount of casein adsorbed to the resin was calculated from the difference between the initial concentration of casein and the residual concentration. For comparison, the adsorption amounts were determined under the same conditions using SA-10A and SA-20A as resins. The results are shown in Figure 5.
[0060] (Reference Examples 1-2 and Reference Comparative Examples 1-2: Adsorption treatment of raw materials containing lactoferrin and casein using an anion exchange resin) An aqueous solution containing lactoferrin and casein was prepared with a lactoferrin concentration of 0.3 g / L and a casein concentration of 20 g / L. 30 g of EGDMA-4VP or EGDMA-TTA / GMA obtained in the synthesis example was added per 100 mL of this aqueous solution as a resin, and the mixture was stirred at 25°C for 30 minutes. The mixture after the treatment was filtered through a filter paper, and the filtrate was centrifuged (5000 g). The residual concentrations of lactoferrin and casein in the supernatant obtained by centrifugation were measured by the ELISA method (described above) using anti-lactoferrin antibody and anti-casein antibody, respectively. The amount of lactoferrin and casein adsorbed to the resin was calculated from the difference between the initial concentration and the residual concentration (Reference Examples 1 to 2). For comparison, the adsorption amounts were determined under the same conditions using SA-10A and SA-20A as resins (Reference Comparative Examples 1 and 2). The results are shown in FIG. 6 (the ratio of the amount of adsorbed casein to the amount of adsorbed lactoferrin is shown in the margin).
Claims
1. The method includes a step of contacting a raw material containing lactoferrin and β-lactoglobulin with an anion exchange resin to selectively adsorb β-lactoglobulin to the anion exchange resin, and a step of recovering a permeate that has permeated the anion exchange resin, The structural unit of the anion exchange resin is represented by the following formula [I] or [II]: 【Chemistry 1】 【Chemistry 2】 It is expressed as In formula [I], m and n each represent a mole number, and the ratio of m to n is 40:60 to 80:20; R 1 is a methyl group, In formula [II], p and q each represent a mole number, and the ratio of p to q is 10:90 to 50:50; Y is a triethylenetetramine residue. A method for producing a product containing lactoferrin at high purity.
2. 2. The method according to claim 1, wherein the raw material further contains casein, and the casein is also selectively adsorbed onto the anion exchange resin in the contact step.
3. The method according to claim 1 or 2, wherein the water content of the anion exchange resin is 40 to 90%.
Citation Information
Patent Citations
JP1975053853A
Removal of lactoglobulin from starting raw material containing whey protein
JP1991019654A
Production of whey protein fraction
JP1994062756A
Phosphoric acid adsorbent
JP2005139414A
Method for separating and recovering whey protein with porous membrane having functional groups interacting with protein
JP2010193833A